2005
DOI: 10.1002/app.20609
|View full text |Cite
|
Sign up to set email alerts
|

Processing and characterization of biodegradable soy plastics: Effects of crosslinking with glyoxal and thermal treatment

Abstract: Processing and modification routes to produce and to improve properties of biodegradable plastics from soy isolate were studied. Soy isolate, acid-treated and crosslinked soy were subsequently compounded, extruded, and injection molded. Acetic acid and glyoxal were examined concerning their suitability for acid treating and crosslinking of soy, and their effect on the final properties of the obtained materials. Heat treatment was also used as a possible methodology to crosslink the protein structure. The molde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…The e-amino group of lysine was considered the primary reactive site between proteins and cross-linkers (Nayudamma et al, 1961). The cross-linkers most extensively used for proteins are aldehydic compounds such as glutaraldehyde (Park et al, 2000;Bigi et al, 2001;Marquié, 2001), formaldehyde (Marquié, 2001) and glyoxal (Vaz, 2005), and epoxy (Patil et al, 2000) and phenolic compounds (Strauss and Gibson, 2004). However, the cytotoxicity of these compounds restricts their use for food covering.…”
Section: Introductionmentioning
confidence: 99%
“…The e-amino group of lysine was considered the primary reactive site between proteins and cross-linkers (Nayudamma et al, 1961). The cross-linkers most extensively used for proteins are aldehydic compounds such as glutaraldehyde (Park et al, 2000;Bigi et al, 2001;Marquié, 2001), formaldehyde (Marquié, 2001) and glyoxal (Vaz, 2005), and epoxy (Patil et al, 2000) and phenolic compounds (Strauss and Gibson, 2004). However, the cytotoxicity of these compounds restricts their use for food covering.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Glutaraldehyde cross-linked chitosan microspheres have shown dynamic storage properties, 16 ion adsorption, 29,30 and immobilization of enzyme 30 and systems for controlled drug delivery. 31,32 Recently other cross-linkers such as genepin [33][34][35] and glyoxal [36][37][38] and other polymers 37 have been examined for their possible applications in the biomedical field, but few studies are reported in which glyoxal is used as the cross-linker in controlled delivery systems. 39 Therefore, in the present investigation, cross-linked chitosan microspheres were prepared at different concentrations of glyoxal and glutaraldehyde using chitosan with different DDAs.…”
Section: Introductionmentioning
confidence: 99%
“…The possible benefits of soy protein include lowering cholesterol, anticarcinogenic effects of Bowman-Birk (BBI), and protective effects against obesity, diabetes, irritants of the digestive tract, bone, and kidney diseases. 20 On the basis of the bioactivity of soy protein, the soy protein plastics prepared by melt-processing 21 and further modification of chemical crosslinking 22 showed a great potential applications as tissue engineering scaffold 23 and drug-delivery system. 22 Additionally, the soy protein-based membrane was also used as drug carrier and wound dressing material.…”
Section: Introductionmentioning
confidence: 99%
“…20 On the basis of the bioactivity of soy protein, the soy protein plastics prepared by melt-processing 21 and further modification of chemical crosslinking 22 showed a great potential applications as tissue engineering scaffold 23 and drug-delivery system. 22 Additionally, the soy protein-based membrane was also used as drug carrier and wound dressing material. 24 To further improve the biofunction and properties, the blending with other biocompatible polymers, such as chitin 25 and chitosan, 26 cellulose, 27 and poly(ethylene glycol), 28 was attempted, and especially produced a new form material of hydrogel for drug delivery.…”
Section: Introductionmentioning
confidence: 99%